2008
DOI: 10.1002/j.0022-0337.2008.72.6.tb04534.x
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Influence Students’ Selection of Advanced Graduate Programs? One Institution's Experience

Abstract: The reasons that students choose certain specialties may be integral to the quality of specialty programs and the future of those specialties. The Harvard School of Dental Medicine (HSDM) has a high percentage (87.6 percent) of students who enroll in postgraduate programs. The goals of this study were to establish a baseline of factors that affect postgraduate program selection at HSDM and to determine if there was a significant difference in factor selection by gender, relationship status, graduation year, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
4
43
4
Order By: Relevance
“…This result means that the specialists formed will maybe not have high levels of clinical skills, or they are useless for the benefit of the population or the patients. Conversely, the influencing factors such as having a competence or talent in a particular field for specialization was very less admitted by the students in this study when compared with others findings (Saeed, Jimenez, Howell, Karimbux, & Sukotjo, 2008;Smith, Lambert, & Goldacre, 2015) in which having a talent in a particular field or possession of special skills was the most popular reason to specialize. However, the prospect of so many more years studying was a discouraging factor as was recently reported (James, Veselina, & Alisa, 2016).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…This result means that the specialists formed will maybe not have high levels of clinical skills, or they are useless for the benefit of the population or the patients. Conversely, the influencing factors such as having a competence or talent in a particular field for specialization was very less admitted by the students in this study when compared with others findings (Saeed, Jimenez, Howell, Karimbux, & Sukotjo, 2008;Smith, Lambert, & Goldacre, 2015) in which having a talent in a particular field or possession of special skills was the most popular reason to specialize. However, the prospect of so many more years studying was a discouraging factor as was recently reported (James, Veselina, & Alisa, 2016).…”
Section: Discussioncontrasting
confidence: 83%
“…Studies views of Japanese, Canadian and Thai undergraduates found that Orthodontics was the most preferred subject in the first two countries, and Oral Surgery in the latter country (Karibe, Suzuki, Sekimoto, Srithavaj, Iamaroon, Warita, Kawakami, Ogata, Shirase, & Nakahara, 2007). In addition, Orthodontics was also the most preferred subject in dental undergraduate's students of USA (Saeed, Jimenez, Howell, Karimbux, & Sukotjo, 2008;Weaver, Chmar, Haden, & Valachovic, 2005). Other findings of involved senior dental students from all dental schools across the USA also reported Orthodontics followed by Oral and Maxillofacial Surgery and Paediatric Dentistry to be the most popular specialties as did for Canada (Gallagher, Patel, & Wilson, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we found that there are currently 13 states where there are no educational measurement programs and some regions of the country, such as the Northeast (14% of total programs), where a limited number of programs currently exist. Although it may be assumed that all students have the ability to relocate for graduate school, previous research has suggested that such an assumption may be untenable, particularly for individuals that have familial responsibilities or place great importance on staying close to their home community (Ramirez, ; Saeed, Jimenez, Howell, Karimbux, & Sukotjo, ). Proctor and Truscott () found that 70% of black school psychologists interviewed reported that the location of the program had a major impact on their decision to attend their doctoral program—mostly due to familial responsibilities and the need to be close to family.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the tendency of majority of students to prefer to continue their education towards a specialty degree [3][4][5][6]. In a survey of ten graduating classes at Harvard School of Dental Medicine [7] regarding students' specialty choice and factors influencing that choice the findings were that the largest percentage of students chose "enjoyment of providing the specialty service" as the factor most influencing their specialty choice. "Prior Dental school experience" and "faculty influence" were greater influences for students pursuing specialties other than those pursuing postdoctoral general dentistry.…”
Section: Introductionmentioning
confidence: 99%